Histopathological spectrum of Cervical Lesion”– two and half Year prospective Study in Tertiary Care Center of Chhattisgarh, India - Dr. Pratima Kujur; Dr. Chandrashekhar Indoria; Dr. S. Bagde; Dr. A. Tiwari (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Cervical lesions are the leading cause of morbidity in Indian women and cervical cancer is the second most common cancer in women worldwide next to breast cancer.Objectives: To study the age distribution, the relative frequency of various cervical lesions and histopathological features of cervical lesions.Materials and Methods: This is a two & half years retrospective study of all cervical biopsies and hysterectomy specimens received from September 2017 to March 2020 in the department of pathology.Result: In a total of 485 cases studied 359 (74.1%) cases were non-neoplastic, 107(22%) were preinvasive and 19 (3.9%) cases were malignant. Cervicitis was the most common non-neoplastic lesion and squamous cell carcinoma was the most common cancer.Conclusion: Our study highlights a vast spectrum of cervical lesions and therefore early detection and management of certain lesions can help in reducing morbidity.